Model Pembiayaan Sektor Pertanian Melalui Linkage Program Lembaga Keuangan Syariah - Safaah Restuning Hayati (SHAHIH: Journal of Islamicate Multidisciplinary, 2018)
This research aims to find strategies and models for financing the agricultural sector. This research is a type of qualitative research using SPACE (Strategic Position and Action Evaluation) matrix analysis. The results of the SPACE Matrix analysis concluded that Islamic financial institutions must carry out an aggressive strategy in providing financing for the agricultural sector. Aggressive profile describes a company that is financially strong and has a competitive advantage in a growing and stable industry. The solution offered is Islamic banking must increase financing in the agricultural sector, through the channeling model (linkage program) with Islamic microfinance institutions, for example BMT. The alignment of Islamic banks to the agricultural sector (real sector) can be realized by providing agricultural insurance against various risks faced by farmers.